Design and synthesis of analogs of the peptidylnucleoside antibiotics: the mureidomycins - Bender, David Michael, author; Williams, Robert M., advisor (Colorado State University. Libraries, 1998)
The recent emergence of strains of bacteria which are resistant to many commercially available antibiotics requires a continual search for new drugs to combat infection. A new family of antibiotics, the mureidomycins, has recently been reported. These compounds have been shown exhibit activity against Pseudomonas aeruginosa through inhibition of phospho-N-acetylmuramyl translocase, an enzyme involved in the lipid cycle of peptidolycan biosynthesis. Progress toward the total synthesis of this series of natural products is described. Specifically, methodology for the production of 4',5'-unsaturated enamine nucleosides has been investigated. In addition, two unnatural amino acids, (S)-m-tyrosine and 2-amino-3-N-methylaminobuyric acid, have been synthesized in optically pure form. Molecular modeling was used to predict structural analogs of the mureidomycin antibiotics. These compounds are simple peptidylnucleosides and are derived from coupling of small amino acid subunits to an aminonucleoside core. The synthesis of these analogs is described, including a novel route to 3',5' -dideoxy-5'aminouridine.
Keywords: Peptide antibiotics